2018
DOI: 10.1111/sms.13210
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic inhibition decreases when estrogen level rises

Abstract: The objective was to determine estrogen's influence on control of a skeletal muscle through measurements of motorneuron excitability (H:M ratio) and presynaptic inhibition (PI). Estrogen serum concentrations were measured at menses and ovulation of female subjects and compared to male controls. Data were analyzed from 12 women and 13 men reporting no history of knee ligament injury. Women reported regular menstrual cycles and no hormone-based contraceptive use for the previous year. Women were tested at menses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Alterations in the levels of neuroactive sex hormones, such as oestradiol and progesterone, might also provide a partial explanation to such discrepant findings. However, with the exception of one experimental design in which the female H max /M max ratio was shown to be higher in conditions compatible with similar levels of oestrogen and progesterone between sexes (Hoffman et al., 2017), no other studies were able to replicate these findings (Hoffman et al., 2008, 2018). In fact, in one of these reports it was even shown that the average correlation between hormones and the H max /M max ratio was close to zero, and that this occurred similarly in both men and women (Hoffman et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alterations in the levels of neuroactive sex hormones, such as oestradiol and progesterone, might also provide a partial explanation to such discrepant findings. However, with the exception of one experimental design in which the female H max /M max ratio was shown to be higher in conditions compatible with similar levels of oestrogen and progesterone between sexes (Hoffman et al., 2017), no other studies were able to replicate these findings (Hoffman et al., 2008, 2018). In fact, in one of these reports it was even shown that the average correlation between hormones and the H max /M max ratio was close to zero, and that this occurred similarly in both men and women (Hoffman et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not control for the effects of the menstrual cycle on H‐reflex excitability. Even though there is some evidence that acute fluctuations of endogenous oestradiol and progesterone do not modulate H‐reflex excitability (Casey et al., 2016), it has also been shown that changes in oestrogen during the menstrual cycle interact with presynaptic inhibition (Hoffman et al., 2018). Presynaptic inhibition exerts a strong influence on H‐reflex excitability (Knikou, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations